Assessment of the drug loading, in vitro and in vivo release behavior of novel pH-sensitive hydrogel. (2nd January 2016) - Dong, Kai; Dong, Yalin; You, Cuiyu; Xu, Wei; Huang, Xiaoyan; Yan, Yan; Zhang, Lu; Wang, Ke; Xing, Jianfeng
Abstract: Context : As a glucocorticoid drug, dexamethasone has good therapeutic effects for ulcerative colitis. pH-sensitive hydrogels could make conventional changes of volume in response with different pH values. Meanwhile, they could load drugs depending on its internal three-dimensional network structure. Objective : Appropriate methods were used to improve the drug-loading capacity of hydrogel and exploring the colon-targeting character of dexamethasone hydrogel. Materials and methods : Different solvents (ethanol and 1, 2-propanediol) were employed to dissolve dexamethasone as well as hydrogel monomer materials (poly(ethylene glycol) methyl ether (MPEG)–poly(lactide acid)–acryloyl chloride macromonomer, itaconic acid (IA) and MPEG–methacrylate), then mixing them together to prepare hydrogel through the heat-initiated free radical polymerization method. Differential scanning calorimetry and X-ray diffraction methods were used to verify whether dexamethasone was loaded into hydrogels. In vitro drug release behavior and in vivo pharmacokinetic study were also investigated in detail. Results : Dexamethasone was successfully loaded into hydrogel, and its loading capacity was improved (5 mg/g). Both the in vitro release study and the in vivo pharmacokinetic study showed the good colon-targeting character of the pH-sensitive P(LE–IA–MEG) hydrogel (Tmax  = 1.0 h, Cmax  = 2.16 µg/ml of dexamethasone; Tmax  = 3.9 h, Cmax  = 0.43 µg/ml of dexamethasone hydrogel). Discussion : Dexamethasone could be targeted to the colon site by P(LE–IA–MEG) hydrogel, thereby improving its therapeutic effect and reduce its side effects. Conclusion : P(LE–IA–MEG) hydrogel might have great potential application in colon-targeted drug delivery systems.